Fertilization with nickel and molybdenum in soybean: effect on agronomic characteristics and grain quality. - Carlim, Edimar Lucasynski; Meert, Leandro; Reis, Bruno; Ercoli, Luciana (REVISTA TERRA LATINOAMERICANA, 2019)
Soybean is one of the most valuable oilseeds in the world, an important source of protein for animal and human food. Correct management of fertilization is essential, especially nitrogen (N), which is demanded in greater quantity. Molybdenum (Mo) and nickel (Ni) are essential micronutrients for the plant and are directly involved in the N cycle and production of amino acids. The objective of this work was to evaluate the effect of applying Mo and Ni on soybean yield components, crop yield, N assimilation and protein yield. Applying Ni and Mo, individually reduced the insertion height of the f irst pod, and Ni and Ni + Mo signif icantly increased stem diameter. Application of Ni associated with Mo resulted in a 12% crop yield increase, as well as a 6% higher protein content, relative to the control. The highest protein content was obtained by combining the two nutrients. Thus, application of Ni in association with Mo is a viable alternative in the production of soybean.